2022
DOI: 10.3390/su14010521
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends on Climate Change and Circular Economy from a Knowledge Mapping Perspective

Abstract: The circular economy (CE) has been proposed as a potentially significant catalyst to enhance the current response to the global climate crisis. The objective of this study was to investigate the scientific literature of the research between climate change and CE adopting a knowledge mapping approach. Based on a total of 789 peer-reviewed publications extracted from Scopus, we found that research on climate change and CE is continually growing and interdisciplinary in nature. Europe notably leads scientific pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…In a circular economy, resources are used, reused, and redeveloped in a closed loop, rather than being extracted, used, and abandoned as waste. In order to enhance the current response to the global climate crisis, Romero-Perdomo et al (2022) propose the circular economy (CE) as a potentially significant facilitator. The author examines the scientific literature on the research between climate change and CE adopting a knowledge mapping approach.…”
Section: Circular Economy (Ce)mentioning
confidence: 99%
“…In a circular economy, resources are used, reused, and redeveloped in a closed loop, rather than being extracted, used, and abandoned as waste. In order to enhance the current response to the global climate crisis, Romero-Perdomo et al (2022) propose the circular economy (CE) as a potentially significant facilitator. The author examines the scientific literature on the research between climate change and CE adopting a knowledge mapping approach.…”
Section: Circular Economy (Ce)mentioning
confidence: 99%
“…As the keyword "greenhouse" can be used in the context of both protected agriculture and climate change, it was necessary to use a fourth parenthesis to avoid retrieving off-topic posts (e.g., "greenhouse effect") using the Boolean operator "AND NOT". The truncation symbol (*) was also used to find both singular and plural words, and the proximity operator (" ") was used to find an exact sentence [20]. The defined search query is shown in Table 1.…”
Section: Analysis Of the Thematic Structure Of The Publicationsmentioning
confidence: 99%
“…Circular research on energy resources has shown progress in substituting fossil fuels for bioenergy sources to improve the microclimatic management of greenhouses and thus reduce greenhouse gases [55]. This need has drawn attention to the identification that the processes that maintain optimal conditions for plant growth, such as cooling, heating, humidifying, and adding light, emit 96% of the greenhouse gases produced in protected horticulture models [56].…”
Section: Knowledge Dissemination and Research Progressmentioning
confidence: 99%